2011
DOI: 10.1007/s00251-011-0565-1
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of the KIR gene cluster in an urban Brazilian population

Abstract: The activity of natural killer cells depends on the balance between activating and inhibitory signals coming from their receptors. Among these are the killer cell immunoglobulin-like receptors (KIR) that recognize specific HLA class I allotypes. Here we characterized KIR genetic diversity and their HLA ligands in the population of Curitiba, Paraná State (n=164), and compared it with other worldwide populations. The distribution of 2DL4 alleles was also analyzed. The Curitiba population did not differ significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
23
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 49 publications
7
23
0
Order By: Relevance
“…Yet the fact that the difference between observed and expected frequencies of KIR genes and their HLA ligands in the present study was close to zero indicates that the selection pressure at least at this level is low. We reported a similar conclusion when analyzing a Brazilian urban population [11].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Yet the fact that the difference between observed and expected frequencies of KIR genes and their HLA ligands in the present study was close to zero indicates that the selection pressure at least at this level is low. We reported a similar conclusion when analyzing a Brazilian urban population [11].…”
Section: Discussionsupporting
confidence: 73%
“…KIR3DL1 recognizes HLA-B and HLA-A molecules with the Bw4 epitope [8] and it has been suggested that KIR3DS1 also binds the Bw4 epitope [9], [10]. Although HLA-B epitopes are currently considered the most important KIR3DL1/S1 ligands, we recently suggested that both HLA-A and B allotypes may be equally important for NK function [11], which corroborates the suggestion about HLA-A and HLA-B having compensatory function in the engagement of KIR receptors and being a KIR-driven functional genetic block [12].…”
Section: Introductionmentioning
confidence: 99%
“…We contribute with two samples for this workshop: Curitiba ( n = 162) is from Southern Brazil (Curitiba, Parana State) of predominantly European ancestry, and its KIR diversity was already reported (Augusto et al ., ,b;); the second one, Campo Grande ( n = 205) from Western Brazil. This population is extensively mixed by European and African ancestries, but also there is a significant Amerindian component.…”
Section: Project Meetingmentioning
confidence: 99%
“…[53,54]. We have previously suggested that although KIR2DL2 313 binds HLA-C ligands with higher affinity than KIR2DL3 [55], relax- Recently, we suggested that both HLA-A and HLA-B could be 342 equally important for KIR recognition [41]. In a remarkable study, 343 Capittini et al [63] …”
mentioning
confidence: 95%
“…Amerindians exhibits a low 40 diversity of KIR gene-content haplotypes when compared to most worldwide population. We compared 41 the KIR-HLA diversity within and between Amerindian groups trying to understand the natural causes of 1. Introduction 51 Killer-cell immunoglobulin-like receptors (KIR) are expressed 52 on the surface of natural killer (NK) cells.…”
mentioning
confidence: 99%